Effects of core strength training on skiing economy in elite junior cross-country skiers - Therell, T.; Jansson, D.; Theos, A. (Research Quarterly for Exercise and Sport, 2022)
Purpose: In cross-country (XC) skiing, the ability to use an efficient technique is essential for performance. The study aimed to compare the effects of supplemental static or dynamic core strength training on skiing economy in elite junior XC skiers. Methods: Twenty-four elite junior XC skiers (14 women, 10 men; 17.8 ± 1.1 years; 67.8 ± 10.0 kg, 173.7 ± 6.4 cm) participated in this study. Participants were allocated either to a static core training (ST) group (n =12) or to a dynamic core training (DT) group (n = 12). Both groups continued their normal aerobic endurance and muscular strength training. Experimental groups performed a 15 minutes, 3 days/week core strength-training program for 9 weeks and in addition to their training. Submaximal and maximal roller ski testing was conducted before and after the 9-week training period. Results: Results showed no significant interaction between groups for energetic costs in any of the submaximal workloads (first, p = .33; second, p =.79; third, p = .25). Pooled data showed a significant improvement in energetic cost pre- to posttesting in the first and third workload (ES 0.40, p = .0006 and ES 0.42, p = .04 respectively). Nine weeks of static or dynamic core strength training in elite junior XC skiers had a small effect on energetic cost in submaximal roller skiing. Conclusion: The type of supplemental core strength training does not seem to affect economy in submaximal roller skiing.